Limited Access to Dermatology Specialty Care: Barriers and Teledermatology - Darlla Duniphin (Dermatology Practical & Conceptual, 2023)
Introduction: Access to dermatology specialty care is limited in the underserved population. Barrier identification and exploring the potential role of teledermatology are the first steps to address this problem.